Endurance athletes and climate change - Nowak, A. S.; Kennelley, G. E.; Krabak, B. J.; Roberts, W. O.; Tenforde, K. M.; Tenforde, A. S. (The Journal of Climate Change and Health, 2022)
Climate change has contributed to increases in the Earth's temperature since the beginning of the industrial age and the warming has accelerated in the last four decades. While climate change has negative impacts on overall global health, more recent events have highlighted the effects on endurance athletes. Endurance athletes primarily train and compete outdoors and are affected by changes in the environment. Notably, climate change contributes to extreme weather, which can result in heat illness; pulmonary disease secondary to air pollution; and an increased risk of infections (i.e., tick-borne and mosquito-borne illness) due to habitat alterations. Elevated environmental temperatures can lead to exertional heat illness (heat exhaustion, heat injury, and heat stroke) and contribute to dehydration with electrolyte disturbances. Hot, dry environments also increase the number and severity of wildfires that affect weather patterns and raise the amount of particulate matter in the air, contributing to air pollution and pulmonary issues. Lyme disease is now the most common tick vector-borne disease and climate change is expanding the geography that harbors tick species carrying the infectious agent. For these reasons, endurance athletes are a unique population to explore the impacts of climate change on sport participation and illness. As governments, sports organizations, multinational corporations, and others address the impact of climate change, athletes, coaches, race organizations, and healthcare providers should begin to consider strategies that mitigate the health concerns of climate change related to training and competitions.